Determinan Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Moderasi - Hermayanti, Citra Pramita; Widodo, Condro (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to analyze profitability as a moderating variable in the relationship between Environmental Social Governance (ESG) and intellectual capital on company value. The research subjects include companies listed on the SRI-KEHATI index from 2020 to 2024. The approach used in this study is a quantitative method, with purposive sampling as the sample selection method. The data obtained from the study were analyzed using STATA 17 software. The findings of the study reveal several important points: 1. ESG has a negative impact on firm value (P> | t | = 0.009 and coefficient = -0.028108). This indicates that the implementation of ESG is perceived by some investors as a significant cost burden, thus considered less beneficial for the company. 2. Intellectual capital has a positive effect on increasing company value (P>| t | = 0.000 and coefficient = 0.0192242), 3. Profitability is proven to strengthen the influence of ESG on company value (P>| t | = 0.003), and 4. Profitability has been proven to strengthen the influence of intellectual capital on company value (P>| t | = 0.000). The conclusion of the hypotheses is that H1 is rejected, while H2, H3, and H4 are accepted